Crematorium. Irkutsk history - Demkov, Sergey (project baikal, 2025)
The article is devoted to the design of a crematorium complex in Irkutsk. It describes the exterior of the crematorium and functional division of its territory, as well as its characteristics in comparison with the capital and foreign analogues.
Keywords: columbarium; crematorium; Irkutsk; ritual zone; territory; master plan